Effects of different divalent cations in mTi-based codopants (m = Mg or Zn) on the piezoelectric properties of AlN thin films - Anggraini, Sri Ayu; Uehara, Masato; Hirata, Kenji; Yamada, Hiroshi; Akiyama, Morito (Ceramics international, 2020)
The understanding of the effects of different divalent cations in codopants for AlN is important for the design of high-performance AlN-based piezoelectric thin films. The addition of Mg-based codopants (e.g., MgTi) into AlN has been one of the most effective methods for the promotion of a higher piezoelectric response (d33). In this study, Mg was replaced by Zn as the divalent cation in a single dopant or codopant and the effects on the piezoelectric responses were investigated. The substitution of Mg with Zn in a single dopant or codopant affected the crystallinity, composition, and eventually d33 of the thin film.